STUDENTS’ PERSONAL CHARACTERISTICS AND DIFFERENCES IN THEIR LEARNING STYLE PREFERENCES IN PUBLIC COLLEGES OF EDUCATION IN THE CENTRAL-WESTERN ZONE OF GHANA - Esia-Donkoh, Kweku (PEOPLE: International Journal of Social Sciences, 2019)
The study investigated the differences in learning style preferences of students of public Colleges of Education (CoEs) in the Central-Western Zone of Ghana based on their personal characteristics (sex, level of study and college setting), and how these personal characteristics influence the students’ choice of learning style preference. The study adopted the cross-sectional survey design. Purposive and random sampling techniques were used to sample 1,396 students from five public CoEs. Frequencies with percentages, independent samples t-test, and regression and ANOVA were used to analyse the data. Generally, a combination of visual, auditory and kinaesthetic learning styles were preferred by the students. Statistically significant differences in the learning style preferences of the students in terms of their sex and setting of college were observed. However, there were no statistically significant differences in the students’ learning style preferences based on their level of study. Again, a statistically significant positive influence of students’ demographic variables on their learning style preferences was established even though the influence was very small. It was concluded that most of the students prefer the use of more than one learning style, and so tutors must comprehend differentiated learning of their students in order to adopt different teaching and assessment techniques to suit the learning needs of the students. It was recommended among others that tutors should encourage students to adopt multiple learning styles and effective study habits to enhance their academic endeavours.